Análise das bandas de frequência do sinal eletromiográfico durante o treinamento de resistência com carga baixa e alta: ensaio clínico randomizado, cego - Azevedo, Jônatas Bezerra de (2021)
Introduction: The use of the electromyographic signal frequency (EMG) has been used as an effective tool to explore the movement motor control strategy. Thus, the frequency band of the EMG signal can reveal relevant physiological information about muscle activity, as it is a measure that allows separating the frequency spectrum of the signal into different bands, that is, different values. Study objective 1: To verify the behavior of the BF of the EMG signal at different strength levels. Study objective 2: To verify the behavior of the frequency bands of the electromyographic signal during resistance training with low versus high load. Methods: This was a prospective randomized, blinded, study consisting of 16 healthy sedentary individuals aged between 20 and 40 years. Each participant obtained a different training protocol for each biceps brachii muscle (BB) defined by drawing lots, ie: training A: with 40% of the maximum load and training B with 70% of the maximum load. The primary outcome of the study was the different frequency bands of the electromyographic (EMG) signal after resistance training. Secondary outcomes were muscle strength and hypertrophy. The EMG signals from the biceps brachii muscle were collected during 4 different strength levels (20, 40, 60 and 80% of MVC [maximum voluntary contraction]) before and after a training program for hypertrophy. Fast Fourier Transform (FFT) defined with Hamming window (50% overlap), 1024 points was used to analyze the EMG signal. The signal power spectrum was divided into six bands: 5-13, 13-30, 30-60, 60-100, 100-200 Hz and 200-300Hz. Results Study 1: After comparing the power of the different LF, only the strength levels of 20% and 80% of the CVM were linked as frequency ranges between 5-13 Hz and 200 -300 Hz. Results Study 2: A multivariate analysis on the significant differences for the Training vs BF (F= 104.63; P < 0.0001; Eta = 0.41), Training vs Groups vs BF interactions (F= 3.34; P = 0.005; Eta= 0.02 ). Conclusions: Only strength levels of 20% and 80% of CVM influenced the frequency bands of 5-13 Hz and 200 -300 Hz. Resistance training with loads of 40 and 70% of 1RM of the BB muscle increased power in the frequency bands between 13-30 Hz while in the 60-100 Hz and 100-200 Hz bands the power decreased.